PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN GEOGRAFI TERHADAP KEMAMPUAN BERPIKIR KRITIS DALAM PEMECAHAN MASALAH SISWA KELAS XII SMA PERTIWI 1 PADANG - Tri Oktaviani 54661; Afdhal Afdhal (JURNAL BUANA, 2023)
This study aims to see the effect of the Problem Based Learning model on critical thinking skills in problem solving for class XII students of SMA Pertiwi 1 Padang with the material of cooperation developed countries and developing countries. Because21st century learning requires schools to realize student skills that refer to the character of 21st century learning. Critical thinking skills in solving problems must be developed by teachers in the geography learning process. But in reality there are still teachers in schools who use conventional learning models. This research uses experimental research in the form of a quashi experiment. Based on the results of the research that from the results of hypothesis testing, the results obtained tcount > t table where (4,179 > 2,000), which is evidenced by a significant level of = 5% meaning that there is a significant difference between the results of critical thinking skills in problem solving students in the experimental class and the control class. Keywords : Problem Based Learning, quashi experiment, critical thinking skills, 21st century geography learning